3D delineation : a modernisation of drawing methodology for field archaeology - Kimball, Justin J. L., (Access archaeology., 2016)
How can 3D models be integrated more fully alongside other forms of archaeological documentation? This work presents a method that combines the interpretative power of traditional archaeological drawings and the realistic visualisation capacity of 3D digital models.